Determinantes sociais do diabetes autorreferido no Brasil - Lima Filho, José Carlos Monteiro (2023)
Diabetes is a non communicable chronic disease that causes serious damage to people's health, putting pressure on health and social care systems. It is important, therefore, to understand the factors that contribute to the higher prevalence of this disease as a way of p roviding relevant information for the formatting of effective public policies in the fight against this disease. In this sense, the present study analyzes, using Logit Models, the variables that influence the probability of occurrence of self reported diab etes in the Brazilian adult population. Models were estimated for the different income quintiles, as a way of verifying whether there is a difference in the effects of the regressors along the income distribution. Additionally, a diabetes concentration cur ve was constructed for the population sorted according to body mass index (BMI). Data come from the National Health Survey PNS 2019, carried out by the Brazilian Institute of Geography and Statistics (IBGE). The results indicate that the practice of physical activity decreases the chance of being diagnosed with diabetes in all income quintiles. In turn, living in an urban area, spending more than three hours a day watching TV, having high blood pressure and being overweight are risk factors for diabetes. Being a woman decreases the likelihood of diabetes only in the richest quintile of the population. In addition, it was found that a higher concentration of diabetes diagnoses was found in the population with a higher BMI, corroborating the fact that being overweight is a risk factor for the accumulation of sugar in the blood.